A Mixed Methods, Exploratory Clinical Case Study of a Monolingual Spanish Speaker: An Investigation of the Feasibility of the Lidcombe Program in an Unexamined Population. - Boult, Johanna R.W.; Hayes, Sandra; Huff, Hannah; Ratcliff, Graeson (Journal of Monolingual & Bilingual Speech (JMBS), 2026)
Considering the cultural and linguistic mismatch between speech-language pathologist (SLP) demographic characteristics and those of a relatively diverse client population, it is likely that monolingual English-speaking SLPs will encounter Spanish-speaking clients who stutter. Treatment efficacy data for stuttering in Spanish-speaking populations is needed in general, and for the Lidcombe Program (the Lidcombe) in particular. Although behavioral contingencies are the treatment variables purported to be at work within the Lidcombe, additional variables likely contribute. Based on the Lidcombe's purported success with English speakers and a few languages other than English, this research aimed to investigate its feasibility with a monolingual Spanish speaker. This study used a mixed methods exploratory case study design, specifically: (i) Qualitative narrative methodology to adequately describe the story of a Spanish-speaking child with a reported history of stuttering, and (ii) a clinical case report. The treatment procedures utilized a monolingual English-speaking clinician working in collaboration with the participant's bilingual mother as a non-neutral interpreter. Outcomes were measured in terms of percent syllables stuttered based on fluency samples and subjective stuttering severity, as judged by the clinician (in the clinical setting) and the participant's mother (in the home setting). Pre-post-treatment comparisons revealed both reduced percent syllables stuttered and reduced severity ratings. This study shows preliminary evidence that the Lidcombe is a feasible treatment delivery option via a monolingual clinician and a monolingual Spanish-speaking client with the mediation of a bilingual parent serving as interpreter. Furthermore, the Lidcombe Program's effect on fluency of children who stutter appears to be inclusive of monolingual Spanish speakers. However, as the Lidcombe's behavioral contingencies alone are likely not explanatory, additional qualitative and mixed methods studies with various sociocultural populations could be useful in pinpointing the true interactional variables that lead to increased fluency.